Influencing factors of the outcome of patients with haemophilia after knee replacement–a retrospective study - Hongyu Jiang; Xueke Chang; Fubin Yu; Ming Zhang; Yifan Liu; Jianzhi Man; Kangshu Guo; Hongzheng Meng; Wenqiang Zhang (BMC Musculoskeletal Disorders)
Abstract Objective To explore the factors that affect the efficacy of knee replacement surgery in hemophiliacs. Methods A retrospective analysis was conducted on 87 patients with hemophilia (PWH) (117knees) who underwent knee arthroplasty in our hospital from January 2012 to December 2020 (mean follow-up 70.8 ± 22 months). General information, hemophilia information, surgical information, follow-up information and psychological assessment information were collected. The knee joint efficacy was evaluated using the Hospital for Special Surgery (HSS) knee score, the American Knee Society’s Clinical (KSC) and Functional (KSF) scores, flexion contracture degree (FC), range of motion (ROM), and wound healing. The excellent and poor groups were divided based on these factors. Logistic regression analysis was used to analyze factors that may affect the knee joint efficacy of patients. Results Seventy-four cases of excellent knee joints and 43 cases of poor knee joints were included. Single factor analysis: The pre-ROM, SF-12MCS, HSS, KSF, and KSC of the excellent group were significantly higher than those of the poor group (P < 0.05); the Hamilton Depression Scale (HAMD), Preoperative Visual Analogue Scale(Pre-VAS), pre-FC degree of the excellent group were significantly lower than those of the poor group (P < 0.05). The proportion of patients undergoing Simultaneous bilateral knee replacement, severe hemophilia, and quadricepsplasty during surgery in the excellent group was significantly lower than that in the poor group (P < 0.05). Logistic regression: Pre-ROM and Simultaneous bilateral knee replacement are independent risk factors affecting knee joint efficacy. Pre-ROM is positively correlated with knee joint efficacy, while Simultaneous bilateral knee replacement is negatively correlated. Conclusion In PWH, the efficacy of knee replacement surgery is related to preoperative ROM and Simultaneous bilateral knee replacement. Better preoperative knee joint mobility is associated with improved outcomes, whereas Simultaneous bilateral knee replacement negatively impacts surgical efficacy.